RANCANG BANGUN SISTEM PENGARSIPAN DATA JAMINAN PESERTA (STUDI KASUS BPJS KETENAGAKERJAAN CIKOKOL TANGERANG) - Sri Rahayu; Ilamsyah Ilamsyah; Riena Eka Putri (Jurnal Sistem Informasi dan Informatika (Simika), 2019)
Archiving data is needed for data handling, archiving will make it easier for companies to add and search for the data needed. The filing system that runs today is in the form of archive files that are stored specifically, by utilizing Microsoft Excel as an application to support its activities. This is considered not effective, because it can trigger data confusion and reporting to existing records. So it is necessary to design of an archiving system that can support performance. With a computerized filing system, it will facilitate archiving in managing archival data, especially in the guarantee section. Data collection methods are carried out by conducting observations, interviews and literature studies from various previous studies. While the system analysis method uses SWOT (Strength, Weakness, Opportunities, Treathment). To design a system using UML modeling (Unified Modeling Language) which is described by usecase diagrams, activity diagrams, sequence diagrams, and Class Diagrams to describe the database relations. The conclusion of this study is to build a web system that is integrated with the database in the filing section, making the archive data collection process more accurate and informative.